1985
DOI: 10.1016/0013-4686(85)80012-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of passivation and pitting corrosion of polycrystalline copper in borate buffer solutions containing sodium chloride

Abstract: The pitting corrosion of copper in borate buffer containing sodium chloride is studied by using potentiostatic and potentiodynamic techniques complemented mth scanning electron microscopy and EDAX. The breakdown potential shifts towards more negative values as the sodium chloride concentration increases. During pitting both soluble Cu(I) and Cu(I1) species are detected. The first stage of pitting is explained through the competition between the passive layer formation and the nucleation and growth of the CuCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 25 publications
3
85
0
Order By: Relevance
“…12, merely loose contour with time after the immersion of the electrode. Similar developments of cyclic voltammograms are described in the literature (see [20,22]). Surface reconstruction caused by adsorbates is well known from ultra-high vacuum studies [24].…”
Section: Discussionmentioning
confidence: 79%
“…12, merely loose contour with time after the immersion of the electrode. Similar developments of cyclic voltammograms are described in the literature (see [20,22]). Surface reconstruction caused by adsorbates is well known from ultra-high vacuum studies [24].…”
Section: Discussionmentioning
confidence: 79%
“…The corrosion potentials observed for a-brasses in neutral chloride solutions are very far from the theoretical values for CulCuCl couple, in contrast to neutral bromide and iodide solutions, so the presence of CuCl is doubtful. According to De Chialvo et al [34], the formation of CuCl occurs at more noble potentials than the corrosion potential.Thus the shift of the corrosion potential to more negative values may be connected with the adsorption of C1-ions onto the metal surface [35]. Such process is assumed to be the first step in the pitting corrosion [36].…”
Section: Methodsmentioning
confidence: 98%
“…17 The interactions of copper oxides with complexing ions such as Cl − are rather complicated. 7,[23][24][25][26] Consequences of such interaction may be a localized attack, with loss of the oxide film. [27][28][29] Previous experimental studies repetitively showed that the presence of Cl − in the electrolyte leads to pitting corrosion, and thus instability of the oxide film, resulting in CuCl formation.…”
Section: -11mentioning
confidence: 99%